Method for enhancing interface performance of carbon fiber composite coating through two-step chemical reaction synergistic modification, modified carbon fiber and application
Through the two-step chemical reaction collaborative modification method, carbon fibers are silanized and hyperbranched to form a modulus gradient transition layer, solving the problem of interface failure of carbon fiber composite coatings in the marine environment and significantly improving its in the marine environment performance and lifespan in.
Patent Information
- Application Number
- CN202411666433.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Due to interface failure problems in marine environments, carbon fiber composite coatings are difficult to meet the corrosion protection needs of steel structure facilities, resulting in a shortened service life.
The two-step chemical reaction collaborative modification method is used to silylation modification and hyperbranching modification of the oxidized carbon fibers to prepare modified carbon fibers to form a modulus gradient transition layer to improve interface performance.
It significantly improves the wetting and adhesion between carbon fiber and resin, extends the service life of the composite coating, and improves its mechanical properties, corrosion resistance and friction wear resistance.
Smart Images

Figure CN119507197A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon fiber reinforced erosion-resistant composite coatings for service in complex and harsh marine environments such as wave splash zones, and relates to a method for modifying carbon fibers, and specifically to a method for synergistically modifying and enhancing the interface performance of carbon fiber composite coatings through a two-step chemical reaction, the obtained modified carbon fibers, and applications thereof. Background Art
[0002] In the splash zone, steel structures are in a state of alternating dry and wet conditions for a long time due to periodic wetting by seawater. Under the combined effects of waves, sunlight, and sufficient oxygen, the corrosion rate of steel structures in the splash zone is the fastest and the degree is the deepest. In particular, seawater carrying air and sediment will continuously wash and wear steel structures at high speed. Under the coupling of multiple corrosion factors, the damage rate of steel structures is greatly accelerated, resulting in structural fracture and destruction, and the service life is greatly shortened.
[0003] Carbon fiber reinforced composite coatings have shown great application potential in the field of corrosion protection of metal materials in marine environments due to their excellent mechanical strength, heat resistance, corrosion resistance, friction resistance and impact resistance. However, the surface of untreated carbon fiber is smooth and the number of active functional groups is small, which makes it difficult for the carbon fiber to be well infiltrated in the resin matrix. The bonding strength of the two is difficult to support the burden of using composite coatings to meet the needs of metal corrosion protection. Due to the poor compatibility of the carbon fiber / resin matrix interface, the load cannot be effectively transferred from the matrix to the carbon fiber, so interface failure is prone to occur at the carbon fiber / resin interface, and stress concentration is formed at the interface defects of the carbon fiber / resin matrix, thereby generating microcracks. The further expansion of the microcracks leads to the complete failure of the composite coating, which seriously limits the high performance of the composite coating. Therefore, the interface failure problem is a key scientific issue for carbon fiber composite coatings to serve in marine environments. Designing and developing carbon fiber composite coatings that synergistically enhance interface performance through mechanical meshing and chemical bonding has become an important topic in the current research on the interface of carbon fiber reinforced composite coatings.
[0004] At present, the strategies for strengthening the interface between carbon fiber and resin in carbon fiber reinforced composite coatings mainly include the following three aspects: oxidation treatment, surface chemical modification and grafted nanoparticles. Oxidation treatment is to etch carbon fiber by electrochemical etching or plasma impact, so that the surface roughness and active functional groups of carbon fiber are improved to improve compatibility with resin, but it will damage the carbon fiber and reduce the original mechanical strength of carbon fiber; while grafted nanoparticles are to assemble carbon nanotubes, graphene and other nanomaterials on the surface of carbon fiber to improve the surface roughness, surface energy, wettability and other properties of carbon fiber, thereby improving the interface bonding strength with the matrix, but it is difficult to achieve mass production due to high cost and harsh production conditions. Therefore, it is urgent to develop a more mild and efficient carbon fiber surface modification method to prepare a carbon fiber reinforced composite coating with strong interface bonding to meet the mechanical properties, erosion resistance and friction and wear resistance required in harsh environments such as ocean splash zones. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for enhancing the interface performance of a carbon fiber composite coating by synergistic modification through a two-step chemical reaction, so as to overcome the deficiencies in the prior art.
[0006] Another object of the present invention is to provide modified carbon fiber obtained by the method.
[0007] Another object of the present invention is to provide a carbon fiber reinforced composite coating and a preparation method and application thereof.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0009] The embodiment of the present invention provides a method for synergistically modifying and enhancing the interface performance of a carbon fiber composite coating by a two-step chemical reaction, which comprises: performing silanization modification and hyperbranching modification on the carbon fiber after oxidation treatment to obtain modified carbon fiber.
[0010] In some embodiments, before the hyperbranched modification treatment is performed, a pretreatment of the hyperbranched modification treatment is performed; the pretreatment includes: grafting polyisocyanate onto the surface of the carbon fiber to obtain isocyanate-grafted carbon fiber;
[0011] The hyperbranched modification treatment comprises: in a protective atmosphere, carrying out a hyperbranched polymerization reaction between imidazole and carbon fiber grafted with isocyanate to obtain carbon fiber grafted with hyperbranched polyimidazole.
[0012] In some embodiments, the silanization modification treatment includes:
[0013] Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution;
[0014] The carbon fiber is fully contacted with the pre-reaction solution and subjected to reaction grafting to obtain silanized modified carbon fiber grafted with polysiloxane.
[0015] The embodiment of the present invention also provides a modified carbon fiber prepared by the above method, the surface of which has a modulus gradient transition layer.
[0016] The embodiment of the present invention also provides a method for preparing a carbon fiber reinforced composite coating, which comprises:
[0017] Evenly mixing the modified carbon fiber and the resin matrix to form a first mixture;
[0018] Adding a curing agent and a defoaming agent into the first mixture and mixing them evenly to obtain a second mixture;
[0019] The second mixture is applied to the surface of the metal substrate and cured to obtain a carbon fiber reinforced composite coating.
[0020] The embodiment of the present invention also provides a carbon fiber reinforced composite coating prepared by the above preparation method.
[0021] Correspondingly, the embodiment of the present invention also provides the application of the carbon fiber reinforced composite coating in the field of substrate protection.
[0022] Furthermore, the application includes: application of the carbon fiber reinforced composite coating on steel structure facilities serving in the ocean splash zone.
[0023] Compared with the prior art, the beneficial effects of the present invention are at least:
[0024] (1) The carbon fiber surface prepared by the modification method provided by the present invention has uniform polymer grafting, the number of polar functional groups is greatly increased, and the wettability and adhesion between the resin and the carbon fiber are significantly improved, thereby greatly improving the interface performance of the composite coating; and a modulus gradient transition layer is constructed between the carbon fiber and the resin with an unbalanced modulus difference, so that the load can be effectively transferred from the resin to the carbon fiber, avoiding stress concentration and thus extending the service life of the composite coating;
[0025] (2) The carbon fiber reinforced composite coating prepared by the method provided by the present invention has excellent mechanical properties, friction and wear resistance, and erosion and wear resistance, and can effectively curb the corrosion damage behavior of steel structure facilities in the marine environment for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a flow chart of a method for synergistically modifying and enhancing the interfacial properties of a carbon fiber composite coating by two-step chemical reactions in a typical embodiment of the present invention;
[0028] Figure 2 This is a SEM image of the modified carbon fiber obtained by hyperbranching and then silanization in Example 1 of the present invention;
[0029] Figure 3a-Figure 3b The digital photos of the composite coating prepared in Example 1 of the present invention before and after the erosion test;
[0030] Figure 4 This is a SEM image of the carbon fiber modified by silanization and then hyperbranching described in Example 2 of the present invention;
[0031] Figure 5 This is a SEM image of the carbon fiber modified by silanization and then hyperbranching described in Example 3 of the present invention;
[0032] Figure 6 This is a SEM image of the hyperbranched and then silanized modified carbon fiber described in Example 4 of the present invention;
[0033] Figure 7 This is a SEM image of the hyperbranched and then silanized modified carbon fiber described in Example 5 of the present invention;
[0034] Figure 8 This is a SEM image of the silanized and then hyperbranched modified carbon fiber described in Example 7 of the present invention;
[0035] Fig. 9 This is a SEM image of the oxidized carbon fiber described in Comparative Example 1 of the present invention;
[0036] Figure 10a-Figure 10b The digital photos of the composite coating prepared in comparative example 1 of the present invention before and after the erosion test;
[0037] Fig.11 This is a SEM image of the silanized modified carbon fiber described in Comparative Example 2 of the present invention;
[0038] Fig.12 This is a SEM image of the hyperbranched modified carbon fiber described in Comparative Example 3 of the present invention;
[0039] Fig.13This is a comparison chart of the average interface shear strength between the modified carbon fibers and the epoxy resin described in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3;
[0040] Fig.14 This is a comparison chart of average mass loss and average volume loss after erosion test of each carbon fiber composite coating described in Examples 1 to 2 of the present invention and Comparative Examples 1 to 3;
[0041] Fig.15 This is a SEM image of the hyperbranched and then silanized modified carbon fiber in Comparative Example 4 of the present invention that has not been subjected to oxidation treatment. DETAILED DESCRIPTION
[0042] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The method of utilizing two-step chemical reactions to synergistically modify and enhance the interfacial performance of carbon fiber composite coatings includes: dust removal and desizing treatment of carbon fiber, oxidation treatment, and two-step chemical modification treatment. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The technical solution, its implementation process and principle will be further explained as follows.
[0044] Specifically, as one aspect of the technical solution of the present invention, a method for synergistically modifying and enhancing the interfacial performance of a carbon fiber composite coating through a two-step chemical reaction comprises: subjecting the oxidized carbon fiber to a silanization modification and a hyperbranching modification to obtain a modified carbon fiber.
[0045] In some embodiments, before the hyperbranched modification treatment is performed, a pretreatment of the hyperbranched modification treatment is performed; the pretreatment includes: grafting polyisocyanate onto the surface of the carbon fiber to obtain isocyanate-grafted carbon fiber.
[0046] In some preferred embodiments, the temperature used for grafting polyisocyanate onto the surface of carbon fiber is 20° C. to 120° C. and the time is 30 min to 24 h.
[0047] In some more specific embodiments, the pretreatment specifically includes: mixing polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding carbon fiber and a catalyst, and reacting in a protective atmosphere to obtain carbon fiber grafted with isocyanate.
[0048] Furthermore, the concentration of the polyisocyanate in the polyisocyanate solution is 0.05 mol / L to 5 mol / L.
[0049] Furthermore, the mass volume ratio of the catalyst to the first organic solvent is (0 g to 0.5 g): (2 ml to 200 ml).
[0050] In some preferred embodiments, the polyisocyanate includes any one or a combination of two or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, dicyclohexylmethane diisocyanate, etc., and is not limited thereto.
[0051] In some preferred embodiments, the first organic solvent includes any one or a combination of two or more of benzene, xylene, cyclohexanone, acetone, butyl acetate, etc., and is not limited thereto.
[0052] In some preferred embodiments, the catalyst includes any one or a combination of two or more of dibutyltin dilaurate, stannous octoate, tin oleate, etc., and is not limited thereto.
[0053] In some preferred embodiments, the protective atmosphere is composed of a protective gas, which includes any one or a combination of two or more of nitrogen, carbon dioxide, helium, argon, etc., and is not limited thereto.
[0054] In some embodiments, the hyperbranched modification treatment comprises: in a protective atmosphere, subjecting imidazole to a hyperbranched polymerization reaction with carbon fiber grafted with isocyanate to obtain carbon fiber grafted with hyperbranched polyimidazole.
[0055] In some preferred embodiments, the hyperbranched polymerization reaction is carried out at a temperature of 30°C to 100°C and for a time of 30 min to 72 h.
[0056] In some preferred embodiments, the hyperbranched modification treatment specifically includes: mixing imidazole with a first organic solvent to form an imidazole solution, and subjecting the imidazole solution to a hyperbranched polymerization reaction with carbon fibers grafted with isocyanate in a protective atmosphere to obtain carbon fibers grafted with hyperbranched polyimidazole.
[0057] Furthermore, the concentration of imidazole in the imidazole solution is 0.05 mol / L to 5 mol / L.
[0058] Furthermore, the protective atmosphere used in the hyperbranched modification treatment is consistent with that used in the pretreatment.
[0059] In some embodiments, the silanization modification treatment includes:
[0060] Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution;
[0061] The carbon fiber is fully contacted with the pre-reaction solution and subjected to reaction grafting to obtain carbon fiber grafted with polysiloxane.
[0062] In some preferred embodiments, the hydrolysis pre-reaction time of the silane coupling agent is 5 minutes to 4 hours, and the temperature is 10°C to 50°C.
[0063] Furthermore, the volume ratio of the silane coupling agent to water is 13:(1-20).
[0064] In some preferred embodiments, the pH value of the pre-reaction solution is 8-13 when the carbon fiber is added.
[0065] In some preferred embodiments, the silane coupling agent includes any one or a combination of two or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, etc., and is not limited thereto.
[0066] Furthermore, the second organic solvent includes methanol and / or ethanol, etc., but is not limited thereto.
[0067] In some preferred embodiments, the reaction grafting time of the silanized modified carbon fiber is 10 min to 12 h, and the reaction grafting temperature is 20° C. to 70° C.
[0068] In some embodiments, in the method of two-step chemical reaction synergistic modification to enhance the interface performance of carbon fiber composite coating, the order of the hyperbranching modification treatment and the silanization modification treatment of the carbon fiber can be arbitrarily changed.
[0069] For example, Figure 1 As shown, in some more preferred embodiments, the method includes: first performing the hyperbranching modification treatment, and then performing the silanization modification treatment, specifically including:
[0070] performing oxidation treatment on the carbon fiber to obtain oxidized carbon fiber;
[0071] Mixing polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding oxidized carbon fiber and a catalyst, and reacting in a protective atmosphere to obtain carbon fiber grafted with isocyanate;
[0072] Mixing imidazole with a first organic solvent to form an imidazole solution, and subjecting the imidazole solution to a hyperbranched polymerization reaction with the carbon fiber grafted with isocyanate in a protective atmosphere to obtain a carbon fiber grafted with hyperbranched polyimidazole;
[0073] Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution;
[0074] The carbon fiber grafted with hyperbranched polyimidazole is placed in a pre-reaction solution for reaction grafting to obtain a hyperbranched polyimidazole-modified carbon fiber grafted with polysiloxane.
[0075] For example, in some other more preferred embodiments, the method includes: first performing the silanization modification treatment, and then performing the hyperbranching modification treatment, specifically including:
[0076] performing oxidation treatment on the carbon fiber to obtain oxidized carbon fiber;
[0077] Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution;
[0078] placing the oxidized carbon fiber in a pre-reaction solution for reaction grafting to obtain oxidized carbon fiber grafted with polysiloxane;
[0079] Mixing a polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding oxidized carbon fibers grafted with polysiloxane and a catalyst, and reacting in a protective atmosphere to obtain oxidized carbon fibers grafted with isocyanate and polysiloxane;
[0080] The imidazole is mixed with the first organic solvent to form an imidazole solution, and the imidazole solution is subjected to a hyperbranched polymerization reaction with the oxidized carbon fiber grafted with isocyanate and polysiloxane in a protective atmosphere to obtain the polysiloxane-modified carbon fiber grafted with hyperbranched polyimidazole.
[0081] In some preferred embodiments, the oxidation treatment includes: using an oxidant to oxidize the carbon fiber so that the surface of the carbon fiber has polar functional groups, and the polar functional groups include at least any one of hydroxyl, keto, carboxyl, etc.; the oxidant may include any one of fluorine, oxygen, ozone, nitric acid, concentrated sulfuric acid, hypochlorous acid, hydrogen peroxide, potassium permanganate, potassium dichromate, potassium persulfate, etc., or a combination of two or more, and is not limited to this.
[0082] In some preferred embodiments, the method further comprises: before the carbon fibers are subjected to oxidation treatment, the carbon fibers are subjected to dust and pulp removal treatment using an alkaline solution or an organic solvent.
[0083] The organic solvent may include any one or a combination of two or more of acetone, ethanol, cyclohexanone, tetrahydrofuran, toluene, petroleum ether, etc., and is not limited thereto.
[0084] In some preferred embodiments, the carbon fiber includes any one or a combination of two or more of carbon fiber powder, chopped carbon fiber, and carbon fiber cloth, but is not limited thereto.
[0085] In some preferred embodiments, the method for enhancing the interfacial performance of the carbon fiber composite coating by synergistic modification of the two-step chemical reaction is completed according to the four steps of dust removal and pulp removal treatment, oxidation treatment, silanization modification treatment and hyperbranching modification treatment of the carbon fiber, and the specific steps are as follows:
[0086] Dust and pulp removal treatment: the untreated carbon fiber is placed in an alkaline solution (such as sodium hydroxide solution) for cleaning, and the dust-removed carbon fiber is obtained after separation and drying; the dust-removed carbon fiber is then placed in an organic solvent (such as acetone) for cleaning, and the dust-free and pulp-free carbon fiber is obtained after separation and drying.
[0087] Oxidation treatment (i.e. activation): Use an oxidant (such as a mixed aqueous solution of potassium persulfate / silver nitrate) to oxidize the desizing carbon fiber. After the carbon fiber is oxidized, polar functional groups such as hydroxyl, keto, and carboxyl groups are obtained on the surface.
[0088] Two-step chemical modification:
[0089] (1) Hyperbranched modification
[0090] Pretreatment before hyperbranched modification: adding polyisocyanate to a first organic solvent and dispersing it uniformly, then adding dry oxidized carbon fiber and a catalyst, passing a protective gas to remove air and moisture, and then reacting to obtain carbon fiber grafted with isocyanate;
[0091] Hyperbranched polymerization reaction: imidazole is added to the first organic solvent to dissolve to obtain an imidazole solution, which is then added to the reaction system to undergo a hyperbranched polymerization reaction with the carbon fiber grafted with isocyanate in a protective atmosphere, and then separated to obtain the carbon fiber grafted with hyperbranched polyimidazole.
[0092] (2) Silanization modification treatment
[0093] Adding a silane coupling agent and water into a second organic solvent to perform a hydrolysis pre-reaction;
[0094] The hyperbranched polyimidazole modified carbon fiber is placed in a pre-reaction solution for further reaction, and the hyperbranched polyimidazole modified carbon fiber grafted with polysiloxane is obtained after separation.
[0095] As another aspect of the technical solution of the present invention, it relates to modified carbon fiber obtained by the above method.
[0096] In some embodiments, the surface of the modified carbon fiber has a modulus gradient transition layer, and the modulus gradient transition layer includes any one of a hyperbranched polyimidazole layer, a polysiloxane layer, and a superimposed layer of hyperbranched polyimidazole and polysiloxane.
[0097] In some embodiments, the thickness of the modulus gradient transition layer is 20 nm to 2 μm. The thickness of the modulus gradient transition layer on the surface of the carbon fiber can be controlled by changing the time of the two-step chemical modification of the carbon fiber.
[0098] The modified carbon fiber is specifically characterized in that the interface shear strength between the modified carbon fiber monofilament and the resin droplets of 30 μm to 50 μm is 44.1 MPa to 75.3 MPa.
[0099] The carbon fiber surface prepared by the above-mentioned modification method has uniform polymer grafting, a greatly increased number of polar functional groups, and significantly improved wettability and adhesion between the resin and the carbon fiber, thereby greatly improving the interface performance of the composite coating; and a modulus gradient transition layer is constructed between the carbon fiber and the resin with an unbalanced modulus difference, so that the load can be effectively transferred from the resin to the carbon fiber, avoiding stress concentration and thus extending the service life of the composite coating.
[0100] As another aspect of the technical solution of the present invention, a method for preparing a carbon fiber reinforced composite coating involves:
[0101] Evenly mixing the modified carbon fiber and the resin matrix to form a first mixture;
[0102] Adding a curing agent and a defoaming agent into the first mixture and mixing them evenly to obtain a second mixture;
[0103] The second mixture is applied to the surface of the metal substrate and cured to obtain a carbon fiber reinforced composite coating.
[0104] In some preferred embodiments, the mass ratio of the modified carbon fiber to the resin matrix is 1:(14.5-76.5).
[0105] In some preferred embodiments, the mass ratio of the modified carbon fiber to the curing agent is 1:(4-23).
[0106] In some preferred embodiments, the ratio of the mass of the defoaming agent to the total mass of the modified carbon fiber, the resin matrix and the curing agent is (0.001-0.005):1.
[0107] In some preferred embodiments, the composite coating is made of modified carbon fiber, a resin matrix and a curing agent.
[0108] In some preferred embodiments, the resin matrix may include any one or a combination of two or more of epoxy resin, phenolic resin, acrylic resin, polyurethane, unsaturated polyester resin, etc., and is not limited thereto.
[0109] Furthermore, the curing agent may include any one or a combination of two or more of an amine curing agent, an anhydride curing agent, an isocyanate curing agent, and a thiol curing agent, but is not limited thereto.
[0110] Furthermore, the defoaming agent may include any one or a combination of two or more of alcohol defoaming agents, polyether defoaming agents, silicone defoaming agents, etc., but is not limited thereto.
[0111] In some preferred embodiments, the preparation method comprises: uniformly mixing the modified carbon fiber and the resin matrix to form a first mixture, and placing the mixture in a vacuum environment for degassing for 10 min to 30 min.
[0112] In some preferred embodiments, the preparation method comprises: adding a curing agent and a defoaming agent to the first mixture, placing the mixture in a vacuum environment for degassing for 10 to 30 minutes, and obtaining a uniformly dispersed second mixture.
[0113] In some preferred embodiments, the preparation method includes: coating the second mixture on the surface of the metal substrate, placing it at room temperature for 12 hours to 48 hours to cure the coating once, and then placing it in a high temperature environment of 60°C to 100°C for secondary curing for 12 hours to 48 hours to obtain a carbon fiber reinforced composite coating.
[0114] Among them, in some more preferred embodiments, a method for preparing a carbon fiber reinforced composite coating specifically comprises the following steps:
[0115] ① Evenly mixing the modified carbon fiber and the resin matrix to form a first mixture, and placing the mixture in a vacuum environment for degassing for 10 to 30 minutes;
[0116] ② Add the curing agent and the defoaming agent to the first mixture, mix them evenly to obtain a second mixture, and place it in a vacuum environment for degassing for 10 minutes to 30 minutes to obtain a uniformly dispersed carbon fiber reinforced composite coating precursor;
[0117] ③ Coat the carbon fiber reinforced composite coating precursor on the surface of the metal substrate, keep it horizontally at room temperature for 12h to 48h to basically cure the coating, and then place it in a high temperature environment of 60℃ to 100℃ for curing for 12h to 48h to obtain the carbon fiber reinforced composite coating.
[0118] As another aspect of the technical solution of the present invention, it also relates to a carbon fiber reinforced composite coating prepared by the above-mentioned preparation method. The carbon fiber reinforced composite coating prepared by the present invention has excellent mechanical properties, friction and wear resistance, and erosion and wear resistance, and can effectively curb the corrosion damage behavior of steel structure facilities in marine environments for a long time.
[0119] Furthermore, when the thickness of the carbon fiber reinforced composite coating is 3.25 mm to 3.88 mm, the tensile strength thereof is 68.3 MPa to 86.6 MPa.
[0120] Furthermore, the wear rate of the carbon fiber reinforced composite coating after the friction test is 4.4×10 -5 (mm 3 / Nm)~8.0×10 -5 (mm 3 / Nm).
[0121] Furthermore, the mass loss of the carbon fiber reinforced composite coating after the erosion test is 0.60 g to 0.83 g when the mass is 21.99 g to 23.61 g.
[0122] As another aspect of the technical solution of the present invention, it also relates to the application of the carbon fiber reinforced composite coating in the field of substrate protection.
[0123] Wherein, the substrate includes steel structure facilities.
[0124] Specifically, the application includes: application of the carbon fiber reinforced composite coating on steel structure facilities serving in the ocean splash zone.
[0125] In summary, the method provided by the present invention is suitable for improving the interfacial properties of carbon fiber composite coatings. After the modified carbon fiber is mixed with a resin and a curing agent and cured, the obtained carbon fiber composite coating has excellent mechanical properties, wear resistance and erosion and wear resistance, and can effectively reduce the corrosion, scouring and wear damage to steel structure facilities in complex and harsh marine environments such as wave splash zones.
[0126] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0127] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0128] Example 1
[0129] 1. Carbon fiber dust removal and pulp removal
[0130] ①, add 16g sodium hydroxide and 200ml deionized water into a glass container, ultrasonically vibrate for 3min, and obtain a sodium hydroxide solution with a concentration of 2M;
[0131] ②, add 5g of carbon fiber into the sodium hydroxide solution, and then place the glass container containing the mixture of carbon fiber and sodium hydroxide solution in a heating device at 85°C;
[0132] ③. Heat and stir the mixture of carbon fiber and sodium hydroxide solution in process ②, control the stirring speed to 400r / min and maintain for 2h, then stop heating, wait for the mixture to cool to room temperature and filter it to obtain dust-removed carbon fiber;
[0133] ④. Use deionized water to stir and wash the treated carbon fiber, and then filter it, repeat 3 times, put the obtained carbon fiber into a constant temperature drying oven and control the temperature at 100°C for continuous drying for 12 hours to obtain dry dust-free carbon fiber;
[0134] ⑤. Add 5g of dust-removed carbon fiber into a glass container filled with 200ml of acetone, place the glass container in a heating device and set up a reflux device, control the heating temperature to 65°C, stir at a stirring speed of 400r / min for 6h, and then filter and separate the mixture to obtain deslurry carbon fiber;
[0135] ⑥. Soak the deslurried carbon fiber obtained in process ⑤ in deionized water at room temperature, control the stirring speed at 200r / min, stir for 1min, let it stand for 3min to allow the carbon fiber to precipitate, then remove the impurities floating on the water surface and pour it out for suction filtration;
[0136] ⑦. Repeat process ⑥ 3 times to obtain the desizing carbon fiber after washing with deionized water, and then put it into a constant temperature drying oven to control the temperature at 100°C for continuous drying for 12 hours to obtain dry desizing carbon fiber;
[0137] 2. Carbon fiber oxidation treatment
[0138] ①, add 20.65g potassium persulfate, 0.14g silver nitrate and 400ml deionized water into a glass container, and then place the glass container in a heating device at a temperature of 85°C and stir and dissolve for 15min, setting the stirring speed to 700r / min, to obtain a potassium persulfate / silver nitrate mixed aqueous solution;
[0139] ②, add 3g of dried desizing carbon fiber to a mixed aqueous solution of potassium persulfate / silver nitrate, maintain the temperature at 85°C, adjust the stirring speed to 400r / min, continue stirring for 4h, and filter while hot after the reaction is completed to obtain oxidized carbon fiber;
[0140] ③, soak the obtained oxidized carbon fiber in deionized water and stir it at a stirring speed of 200r / min for 5min, then pour it out and filter it for separation;
[0141] ④, repeat process ③ 3 times to obtain the oxidized carbon fiber after washing with deionized water, put it into a constant temperature drying oven set at 100°C and dry it for 12 hours to obtain dry oxidized carbon fiber;
[0142] 3. Hyperbranched modification of carbon fiber
[0143] ①, add 4.95g of isophorone diisocyanate into a glass container filled with 30ml of acetone, disperse by ultrasonic oscillation for 3min, then add 0.5g of dried oxidized carbon fiber and 0.02g of dibutyltin dilaurate, introduce nitrogen to discharge air and moisture in the glass container, and react in a closed environment at a heating temperature of 55°C and a stirring speed of 600r / min for 6h to obtain reaction product I;
[0144] ②, add 1.65g imidazole to 30ml acetone and vortex for 2min to obtain imidazole acetone solution;
[0145] ③, adding the imidazole acetone solution to the reaction product I of process ① at a rate of 3 drops / second, reacting for 24 hours at a temperature of 60°C and a stirring speed of 800 r / min in a closed environment to obtain a uniformly dispersed reaction product II;
[0146] ④. Filter the reaction product II obtained in process ③ to obtain hyperbranched polyimidazole modified carbon fiber, then use 50 ml of methanol and 50 ml of anhydrous ethanol to soak and clean the carbon fiber at room temperature for 5 min at a stirring speed of 200 r / min, repeat the washing twice, filter and separate, put it into a constant temperature drying oven set at 90 ° C and dry it for 24 h to obtain a dry hyperbranched modified carbon fiber;
[0147] 4. Carbon fiber silanization modification treatment
[0148] ①, add 5 ml of 3-aminopropyltriethoxysilane and 90 ml of anhydrous ethanol into a glass container, and stir vigorously at a stirring speed of 800 r / min for 5 min to obtain a 3-aminopropyltriethoxysilane solution;
[0149] ②. Add 5 ml of deionized water to the 3-aminopropyltriethoxysilane solution under vigorous stirring, then adjust the stirring speed to 500 r / min, and react at room temperature for 1 hour to obtain reaction product III;
[0150] ③. The pH of the reaction product III was adjusted to pH = 10, and then 0.5 g of the hyperbranched modified carbon fiber was added to the reaction product III, and stirred at a speed of 400 r / min for 2 h at room temperature to obtain a reaction product IV;
[0151] ④, the reaction product IV was filtered, the obtained carbon fiber was soaked in 100 ml of anhydrous ethanol for 5 minutes and then filtered again, washed and filtered twice, and then placed in a constant temperature drying oven set at 90 ° C for 8 hours to obtain a dried modified carbon fiber that was first hyperbranched and then silanized;
[0152] 5. Preparation of carbon fiber composite coating
[0153] ①, 0.975g of dried modified carbon fiber that was first hyperbranched and then silanized was mixed evenly with 29.25g of GCC135 epoxy resin to form a mixture I, and placed in a -0.1MPa vacuum environment for degassing for 20min;
[0154] ②, 8.775g of GCC137 curing agent and 0.08g of defoaming agent were added to mixture I, and the mixture was evenly mixed to obtain mixture II, which was placed in a -0.1MPa vacuum environment for degassing for 15 minutes to obtain a uniformly dispersed carbon fiber reinforced composite coating;
[0155] ③. Coat the carbon fiber reinforced composite coating described in step ② on the surface of the metal substrate, keep it horizontally at room temperature for 24 hours to allow the coating to be basically cured, and then place it in a high temperature environment of 80°C for 24 hours to obtain the carbon fiber reinforced composite coating.
[0156] Figure 2 The SEM morphology of the modified carbon fiber obtained in this embodiment is shown. It can be seen that the protruding particles are hyperbranched polyimidazole macromolecules grafted on the surface of the carbon fiber through the first step of the chemical reaction, which increases the surface roughness of the carbon fiber and provides more mechanical meshing physical anchor points for the interface between the fiber and the resin; and the carbon fiber and the protruding particles are covered with a layer of aminopropyl polysiloxane grafted on the surface of the carbon fiber through the second step of the chemical reaction. The amino groups on the side chains of the polysiloxane greatly increase the surface energy of the carbon fiber and provide abundant chemical bonding reaction sites. Therefore, the method of synergistic modification by two-step chemical reaction significantly improves the bonding between the carbon fiber and the epoxy resin and enhances the interface performance. Compared with Comparative Examples 1 to 3, the mechanical properties, erosion resistance, and friction and wear resistance of the composite coating prepared in this embodiment are more excellent.
[0157] The microbead debonding test shows that the carbon fiber composite coating prepared in this embodiment has excellent interfacial adhesion, and the interfacial shear strength between the fiber and the resin is 66.23 MPa, which is 58.7% higher than that of the comparative example 1 without the two-step chemical reaction modification treatment, and is also higher than the interfacial shear strength of all other comparative examples (such as Fig.13 As shown in the figure, the data are the average values after 20 tests), which shows that the two-step chemical reaction modification can synergistically enhance the interface performance between carbon fiber and resin, thereby improving the mechanical properties of the composite coating.
[0158] The parameters selected for the erosion test are as follows: the erosion material is a mixture of silicon carbide and water with a mass concentration of 10wt%, the solid-liquid two-phase flow ejection pressure is 0.2MPa, the impact time is 15min, and the impact direction is perpendicular to the coating surface.
[0159] The erosion test shows that the carbon fiber composite coating prepared in this embodiment has excellent erosion and wear resistance. Figure 3a and Figure 3b , Fig.10a and Fig.10b It can be seen that the area of the erosion pits formed on the surface of the composite coating prepared in this embodiment after the erosion test is significantly smaller than that of the erosion pits in comparative example 1. After 15 minutes of high-speed erosion with silicon carbide and water, the mass loss of the composite coating in this embodiment is 629.6 mg, and the volume loss is 380.38 mm 3 , the values are lower than those of the composite coating of the comparative example (such as Fig.14 As shown in the figure, the data in the figure are the average values after 5 tests). The carbon fiber composite coating obtained in Comparative Example 1 has the largest mass and volume loss: the mass loss is 893.4 mg, and the volume loss is 575.97 mm 3 Compared with this, the mass loss of the carbon fiber composite coating in this embodiment is reduced by 29.5%, and the volume loss is reduced by 34%.
[0160] This embodiment illustrates that by synergistically modifying carbon fibers through a two-step chemical reaction of first hyperbranching and then silanization, a modulus gradient transition layer can be constructed on the surface of the carbon fibers, thereby reducing the huge modulus difference between the fibers and the resin, improving the load transfer efficiency, and enhancing the interface performance of the carbon fiber composite coating.
[0161] Example 2
[0162] This embodiment is basically the same as Embodiment 1, except that: Step 3 of this embodiment is a silanization modification of the carbon fiber, and Step 4 is a hyperbranching modification of the carbon fiber, which is the opposite order to that of Embodiment 1.
[0163] like Figure 4 The SEM morphology of the modified carbon fiber obtained in this embodiment is shown. First, the first step of chemical reaction modification treatment grafts a layer of polysiloxane on the surface of the carbon fiber. The rich side chain amino groups of polysiloxane greatly improve the surface energy of the carbon fiber, and at the same time lay the foundation for the subsequent uniform grafting of hyperbranched polyimidazole; in the second step of chemical reaction, the hyperbranched polyimidazole grows in situ with the amino group as the reaction site, and a dense layer of nanoparticles is grafted on the surface of the carbon fiber, which significantly improves the surface roughness and wettability of the carbon fiber, and provides a large number of mechanical meshing anchor points for the subsequent combination with the resin.
[0164] The microbead debonding test shows that the interface shear strength between the modified carbon fiber and the epoxy resin obtained in this embodiment is 65.97 MPa, which is 58.1% higher than that of the comparative example 1 without two-step chemical modification (e.g. Fig.13 shown).
[0165] The erosion test showed that the carbon fiber composite coating lost 663.9 mg in mass and 419.66 mm in volume after the erosion test. 3 The mechanical properties, erosion resistance, and friction and wear resistance are better than those of the comparative examples (such as Fig.14 shown).
[0166] This embodiment illustrates that by changing the order of the two-step chemical reaction, a modulus gradient transition layer can also be constructed on the carbon fiber surface to improve the load transfer efficiency, while greatly improving the bonding between the carbon fiber and the epoxy resin, enhancing the interface performance and thus improving the overall performance of the composite coating.
[0167] Example 3
[0168] This embodiment is substantially the same as Embodiment 2, except that the hyperbranched polymerization reaction time of the carbon fibers in this embodiment is extended from 24 hours to 48 hours.
[0169] like Figure 5 Shown is the SEM morphology of the modified carbon fiber prepared in this example which is first silanized and then hyperbranched.
[0170] This embodiment illustrates that by changing the time of the hyperbranched polymerization reaction, the thickness of the modulus gradient transition layer on the carbon fiber surface can be changed, thereby affecting the overall performance of the composite coating.
[0171] Example 4
[0172] This embodiment is substantially the same as Embodiment 1, except that the polyisocyanate selected in the carbon fiber hyperbranching modification step in this embodiment is hexamethylene diisocyanate instead of isophorone diisocyanate.
[0173] like Figure 6 The SEM morphology of the modified carbon fiber obtained in this example is shown. Compared with the surface morphology of the carbon fiber obtained in Example 1, the morphology and structure of the two are highly similar. The erosion test shows that the mass loss of the composite coating obtained in this example after the erosion test is 655.4 mg, and the erosion resistance is better than that of Example 2.
[0174] This embodiment illustrates that: selecting other polyisocyanates described in claim 4 to be grafted onto the surface of carbon fiber and then undergoing a hyperbranching reaction with imidazole can also effectively improve the surface energy and roughness of the carbon fiber, enhance the interface bonding between the carbon fiber and the resin matrix, and improve the erosion resistance of the composite coating.
[0175] Example 5
[0176] This embodiment is substantially the same as Embodiment 1, except that the silane coupling agent selected in the carbon fiber silanization modification step in this embodiment is 3-aminopropyltrimethoxysilane instead of 3-aminopropyltriethoxysilane.
[0177] like Figure 7 The SEM morphology of the modified carbon fiber obtained in this example is shown. Figure 2 and Figure 7 It was found that the polysiloxane layer on the surface of the modified carbon fiber prepared by first hyperbranching and then silanization using 3-aminopropyltrimethoxysilane was relatively thin, resulting in greater surface roughness. The erosion test showed that the mass loss of the composite coating prepared in this embodiment after the erosion test was 614.5 mg, and the erosion resistance was better than that of Example 1. Grafting 3-aminopropyltrimethoxysilane not only increased the number of active groups on the carbon fiber surface, but also increased the roughness and enhanced the mechanical interlocking between the carbon fiber and the resin matrix.
[0178] This embodiment illustrates that the selection of other silane coupling agents to modify carbon fibers as described in claim 5 can also significantly increase the number of active groups on the carbon fiber surface, enhance the mechanical interlocking and chemical bonding between the carbon fibers and the resin matrix, and thus improve the erosion resistance of the composite coating.
[0179] Example 6
[0180] The processing steps of the modified carbon fiber in this embodiment are exactly the same as those in Example 1, except for the preparation steps of the carbon fiber composite coating. The resin matrix selected in this embodiment is 191 type unsaturated polyester resin, and methyl ethyl ketone peroxide is selected as a curing agent and cobalt isooctanoate is selected as an accelerator, wherein the unsaturated polyester resin: curing agent = 100: 0.8-1.5, and the unsaturated polyester resin: accelerator = 100: 0.5-1. The preparation process of the carbon fiber composite coating is:
[0181] ①, 1 g of dried modified carbon fiber that was first hyperbranched and then silanized, 38.42 g of 191 type unsaturated polyester resin and 0.19 g of accelerator were mixed uniformly to form a mixture I, and placed in a -0.1 MPa vacuum environment for degassing for 10 min;
[0182] ②, adding 0.38g of V388 curing agent to mixture I, mixing evenly to obtain mixture II, and then obtaining a uniformly dispersed carbon fiber reinforced composite coating;
[0183] ③. Pour the carbon fiber reinforced composite coating described in step ② into the mold, keep it horizontally at room temperature for 24 hours to allow the coating to solidify, and then demould to obtain the carbon fiber reinforced composite coating.
[0184] The tensile test shows that the tensile strength of the composite coating prepared in this embodiment is 72.1 MPa, while the tensile strength of the composite coating prepared with oxidized carbon fiber as filler is measured to be 56.8 MPa, compared with which the tensile strength of the composite coating of this embodiment is increased by 26.94%; the mass loss of the composite coating prepared in this embodiment after the erosion test is 726.3 mg, and the mass loss of the composite coating with oxidized carbon fiber as filler is 1218.4 mg. In comparison, the mass loss of the composite coating of this embodiment is reduced by 40.39%, indicating that a modulus gradient transition layer is constructed between the carbon fiber and the resin matrix through two-step chemical modification, which can effectively transfer the load from the resin matrix to the fiber, and the interface bonding between the two is better, so that the mechanical properties and erosion resistance of the composite coating are significantly improved.
[0185] This embodiment illustrates that a composite coating with excellent performance can also be obtained by selecting other resin matrices as described in claim 9 and compounding them with carbon fibers modified by the two-step chemical reaction described in the present invention.
[0186] Example 7
[0187] This embodiment is substantially the same as embodiment 2, except that in this embodiment, the amount of isophorone diisocyanate added in the carbon fiber hyperbranching modification step is 0.495 g.
[0188] like Figure 8 The SEM morphology of the modified carbon fiber prepared in this example is shown. Figure 4 At the same magnification, almost no spherical hyperbranched polyimidazole particles can be observed on the carbon fiber surface. 4 times and observed Figure 4 Same surface structure.
[0189] This example illustrates that changing the concentration of the reactants will change the growth size of the polymer, the degree of grafting on the carbon fiber surface, and the morphology of the carbon fiber surface, thereby affecting the interface bonding between the carbon fiber and the resin matrix and the overall performance of the composite coating.
[0190] Example 8
[0191] This embodiment is basically the same as embodiment 1, except that: the polyisocyanate is lysine diisocyanate, the temperature used to graft the polyisocyanate onto the carbon fiber surface is 20°C and the time is 24h; the concentration of the polyisocyanate is 0.05mol / L, the temperature of the hyperbranched polymerization reaction is 30°C and the time is 72h;
[0192] The temperature of the hydrolysis pre-reaction is 10° C., the time is 4 hours, and the pH value of the pre-reaction solution is 8; the reaction grafting time of the silanized modified carbon fiber is 10 minutes, and the reaction grafting temperature is 70° C.;
[0193] The mass ratio of the modified carbon fiber to the resin matrix is 1:14.5; the mass ratio of the modified carbon fiber to the curing agent is 1:4;
[0194] The coating preparation method includes: coating the second mixture on the surface of the metal substrate, placing the coating at room temperature for 12 hours to cure the coating, and then placing the coating in a 60°C environment for secondary curing for 48 hours to obtain a carbon fiber reinforced composite coating.
[0195] Example 9
[0196] This embodiment is basically the same as embodiment 1, except that: the polyisocyanate is dicyclohexylmethane diisocyanate, the temperature used to graft the polyisocyanate onto the surface of the carbon fiber is 120°C and the time is 30 min; the concentration of the polyisocyanate is 5 mol / L, the temperature of the hyperbranched polymerization reaction is 100°C and the time is 30 min;
[0197] The temperature of the hydrolysis pre-reaction is 50°C, the time is 5 minutes, and the pH value of the pre-reaction solution is 13; the reaction grafting time of the silanized modified carbon fiber is 12 hours, and the reaction grafting temperature is 20°C;
[0198] The mass ratio of the modified carbon fiber to the resin matrix is 1:76.5; the mass ratio of the modified carbon fiber to the curing agent is 1:23;
[0199] The coating preparation method includes: coating the second mixture on the surface of the metal substrate, placing the coating at room temperature for 48 hours to cure the coating, and then placing the coating in a high temperature environment of 100°C for secondary curing for 12 hours to obtain a carbon fiber reinforced composite coating.
[0200] Example 8N9 illustrates: Using different reaction temperatures, reaction times, reaction concentrations and pH values to perform hyperbranching and silanization modification on the fibers can effectively improve the surface roughness and interfacial compatibility of the fibers, improve the interfacial bonding with the resin matrix, and construct a modulus gradient transition layer on the carbon fiber surface, thereby promoting the transfer of stress concentration, effectively inhibiting the initiation and propagation of cracks at the interface, and thereby improving the overall performance and service life of the composite coating.
[0201] Comparative Example 1
[0202] This comparative example is substantially the same as Example 1, except that the carbon fibers in this comparative example are not subjected to silanization and hyperbranching modification treatments after oxidation treatment.
[0203] like Fig. 9Shown is a SEM image of the oxidized carbon fiber in this comparative example. Figure 10a-Figure 10b The digital photos of the composite coating prepared in this comparative example before and after the erosion test. Fig.13 , the mass loss and volume loss comparison of the composite coating after erosion test Fig.14 .
[0204] Comparative Example 2
[0205] This comparative example is basically the same as Example 1, except that the carbon fibers in this comparative example are subjected to silanization modification after oxidation treatment, but not to hyperbranching modification.
[0206] like Fig.11 The SEM image of the silanized modified carbon fiber prepared in this comparative example is shown. The interfacial shear strength between the carbon fiber and the epoxy resin is shown in Fig.13 , the comparison of mass loss and volume loss of the composite coating after erosion test is shown in Fig.14 .
[0207] Comparative Example 3
[0208] This comparative example is basically the same as Example 1, except that the carbon fibers in this comparative example are subjected to hyperbranching modification after oxidation treatment, but not silanization modification.
[0209] like Fig.12 The SEM image of the hyperbranched modified carbon fiber prepared in this comparative example is shown. The interfacial shear strength between the carbon fiber and the epoxy resin is shown in Fig.13 , the comparison of mass loss and volume loss of the composite coating after erosion test is shown in Fig.14 .
[0210] Comparative Examples 1 to 3 illustrate that the interface performance between the carbon fiber and the resin in any one of the two-step modification steps is not as good as that in the two-step modification. At the same time, the mechanical strength, wear resistance and erosion resistance of the obtained composite coating cannot be better improved.
[0211] Comparative Example 4
[0212] This comparative example is substantially the same as Example 1, except that the carbon fibers in this comparative example are not subjected to oxidation treatment.
[0213] like Fig.15 The following is a SEM image of the surface morphology of the carbon fiber obtained in this comparative example. Figure 2 and Fig.15It was found that the carbon fiber surface did not have a morphology similar to that of Example 1 in which a polysiloxane layer wrapped large hyperbranched polyimidazole particles. Instead, a thin polysiloxane layer covered the carbon fiber with a morphology of small polysiloxane particles with protrusions. This is because the oxidation treatment can activate the carbon fiber surface, introduce hydroxyl and carboxyl active functional groups, and provide reaction sites for subsequent hyperbranched modification. Without oxidation treatment, polyisocyanate cannot be grafted to the fiber surface by chemical bonding, and hyperbranched polyimidazole cannot grow in situ on the fiber surface, thereby missing a hyperbranched polyimidazole layer, and only a small amount of hyperbranched polyimidazole particles are deposited on the fiber surface, weakening the modulus gradient transition layer between the carbon fiber and the resin matrix.
[0214] The friction and wear test shows that the wear rate of the composite coating prepared in this comparative example is 7.94×10 -5 (mm 3 / Nm), compared with the composite coating prepared in Comparative Example 2 (7.99×10 -5 (mm 3 The wear rate of the composite coating prepared in Example 1 is close to that of the composite coating prepared in Example 1, but much higher than that of the composite coating prepared in Example 1, which is 5.77×10 -5 (mm 3 / Nm), indicating that the lack of oxidation treatment will reduce the wear resistance of the two-step chemically modified carbon fiber composite coating.
[0215] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0216] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for enhancing the interfacial properties of carbon fiber composite coatings by synergistic modification through two-step chemical reactions, characterized in that: include: The carbon fiber after oxidation treatment is subjected to silanization modification treatment and hyperbranching modification treatment to obtain modified carbon fiber.
2. The method according to claim 1, characterized in that: Before the hyperbranched modification treatment is performed, a pretreatment of the hyperbranched modification treatment is performed; the pretreatment comprises: grafting polyisocyanate onto the surface of the carbon fiber to obtain carbon fiber grafted with isocyanate; The hyperbranched modification treatment comprises: in a protective atmosphere, allowing imidazole and carbon fiber grafted with isocyanate to undergo a hyperbranched polymerization reaction to obtain carbon fiber grafted with hyperbranched polyimidazole; And / or, the silanization modification treatment includes: Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution; The carbon fiber is fully contacted with the pre-reaction solution and subjected to reaction grafting to obtain silanized modified carbon fiber grafted with polysiloxane.
3. The method according to claim 2, characterized in that: The temperature used for grafting polyisocyanate onto the carbon fiber surface is 20°C to 120°C and the time is 30min to 24h; And / or, the hyperbranched polymerization reaction temperature is 30°C to 100°C, and the time is 30min to 72h; And / or, the pretreatment includes: mixing a polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding carbon fiber and a catalyst, and reacting in a protective atmosphere to obtain carbon fiber grafted with isocyanate; And / or, the hyperbranched modification treatment includes: mixing imidazole with a first organic solvent to form an imidazole solution, and subjecting the imidazole solution to a hyperbranched polymerization reaction with the carbon fiber grafted with isocyanate in a protective atmosphere to obtain the carbon fiber grafted with hyperbranched polyimidazole.
4. The method according to claim 3, characterized in that: The concentration of the polyisocyanate in the polyisocyanate solution is 0.05 mol / L to 5 mol / L; and / or the mass volume ratio of the catalyst to the first organic solvent is (0 g to 0.5 g): (2 ml to 200 ml); And / or, the polyisocyanate includes any one or a combination of two or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, and dicyclohexylmethane diisocyanate; And / or, the first organic solvent includes any one or a combination of two or more of benzene, xylene, cyclohexanone, acetone, and butyl acetate; And / or, the catalyst includes any one of dibutyltin dilaurate, stannous octoate, and tin oleate, or a combination of two or more thereof; and / or, the concentration of imidazole in the imidazole solution is 0.05 mol / L to 5 mol / L; And / or, the protective atmosphere is composed of a protective gas, and the protective gas includes any one of nitrogen, carbon dioxide, helium, and argon, or a combination of two or more thereof.
5. The method according to claim 2, characterized in that: The reaction grafting time of the silanized modified carbon fiber is 10 minutes to 12 hours, and the reaction grafting temperature is 20° C. to 70° C.; And / or, the silane coupling agent includes any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, and 3-isocyanatepropyltrimethoxysilane, or a combination of two or more thereof; and / or, the second organic solvent comprises methanol and / or ethanol; And / or, the temperature of the hydrolysis pre-reaction is 10°C to 50°C, and the time is 5min to 4h; And / or, the volume ratio of the silane coupling agent to water is 13:(1-20); And / or, the pH value of the pre-reaction solution is 8-13.
6. The method according to claim 2, characterized in that include: The hyperbranching modification treatment is first performed, and then the silanization modification treatment is performed, which specifically includes: performing oxidation treatment on the carbon fiber to obtain oxidized carbon fiber; Mixing polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding oxidized carbon fiber and a catalyst, and reacting in a protective atmosphere to obtain carbon fiber grafted with isocyanate; Mixing imidazole with a first organic solvent to form an imidazole solution, and subjecting the imidazole solution to a hyperbranched polymerization reaction with the carbon fiber grafted with isocyanate in a protective atmosphere to obtain a carbon fiber grafted with hyperbranched polyimidazole; Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution; Placing the carbon fiber grafted with hyperbranched polyimidazole in a pre-reaction solution for reaction grafting to obtain a hyperbranched polyimidazole-modified carbon fiber grafted with polysiloxane; Alternatively, the method comprises: first performing the silanization modification treatment, and then performing the hyperbranching modification treatment, specifically comprising: performing oxidation treatment on the carbon fiber to obtain oxidized carbon fiber; Mixing a silane coupling agent, water and a second organic solvent to perform a hydrolysis pre-reaction to form a pre-reaction solution; placing the oxidized carbon fiber in a pre-reaction solution for reaction grafting to obtain oxidized carbon fiber grafted with polysiloxane; Mixing a polyisocyanate with a first organic solvent to form a polyisocyanate solution, adding oxidized carbon fibers grafted with polysiloxane and a catalyst, and reacting in a protective atmosphere to obtain oxidized carbon fibers grafted with isocyanate and polysiloxane; Mixing imidazole with a first organic solvent to form an imidazole solution, and subjecting the imidazole solution to a hyperbranched polymerization reaction with an oxidized carbon fiber grafted with isocyanate and polysiloxane in a protective atmosphere to obtain a polysiloxane-modified carbon fiber grafted with hyperbranched polyimidazole; And / or, the oxidation treatment includes: using an oxidant to oxidize the carbon fiber so that the surface of the carbon fiber has polar functional groups, the polar functional groups include at least any one of hydroxyl, ketone, and carboxyl groups, and the oxidant includes any one of fluorine gas, oxygen, ozone, nitric acid, concentrated sulfuric acid, hypochlorous acid, hydrogen peroxide, potassium permanganate, potassium dichromate, and potassium persulfate, or a combination of two or more thereof; And / or, the method further comprises: before the carbon fiber is subjected to oxidation treatment, the carbon fiber is subjected to dust and pulp removal treatment using an alkaline solution or an organic solvent, wherein the organic solvent comprises any one of acetone, ethanol, cyclohexanone, tetrahydrofuran, toluene, and petroleum ether, or a combination of two or more thereof; And / or, the carbon fiber includes any one of carbon fiber powder, chopped carbon fiber and carbon fiber cloth, or a combination of two or more thereof.
7. The modified carbon fiber obtained by the method according to any one of claims 1 to 6, characterized in that: The modified carbon fiber surface has a modulus gradient transition layer, the modulus gradient transition layer includes any one of a hyperbranched polyimidazole layer, a polysiloxane layer, and a superimposed layer of hyperbranched polyimidazole and polysiloxane, and the thickness of the modulus gradient transition layer is 20nm to 2μm; The interface shear strength between the modified carbon fiber monofilament and the resin droplets of 30 μm to 50 μm is 44.1 MPa to 75.3 MPa.
8. A method for preparing a carbon fiber reinforced composite coating, characterized in that: include: Mixing the modified carbon fiber according to claim 7 and a resin matrix uniformly to form a first mixture; Adding a curing agent and a defoaming agent into the first mixture and mixing them evenly to obtain a second mixture; The second mixture is applied to the surface of the metal substrate and cured to obtain a carbon fiber reinforced composite coating.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the modified carbon fiber to the resin matrix is 1:(14.5-76.5); And / or, the mass ratio of the modified carbon fiber to the curing agent is 1:(4-23); And / or, the ratio of the mass of the defoaming agent to the total mass of the modified carbon fiber, the resin matrix and the curing agent is (0.001-0.005):1; And / or, the resin matrix includes any one or a combination of two or more of epoxy resin, phenolic resin, acrylic resin, polyurethane, and unsaturated polyester resin; And / or, the curing agent includes any one or a combination of two or more of an amine curing agent, an anhydride curing agent, an isocyanate curing agent, and a thiol curing agent; And / or, the defoamer includes any one of an alcohol defoamer, a polyether defoamer, and a silicone defoamer, or a combination of two or more thereof; And / or, the preparation method comprises: uniformly mixing the modified carbon fiber and the resin matrix to form a first mixture, and placing the mixture in a vacuum environment for degassing for 10 min to 30 min; And / or, the preparation method comprises: adding a curing agent and a defoaming agent to the first mixture, placing the mixture in a vacuum environment for degassing for 10 minutes to 30 minutes, and obtaining a uniformly dispersed second mixture; And / or, the preparation method includes: coating the second mixture on the surface of the metal substrate, placing it at room temperature for 12 hours to 48 hours to cure the coating once, and then placing it in a high temperature environment of 60°C to 100°C for secondary curing for 12 hours to 48 hours to obtain a carbon fiber reinforced composite coating.
10. The carbon fiber reinforced composite coating prepared by the preparation method according to any one of claims 8 to 9, characterized in that: When the thickness of the carbon fiber reinforced composite coating is 3.25 mm to 3.88 mm, the tensile strength is 68.3 MPa to 86.6 MPa; The wear rate of the carbon fiber reinforced composite coating after the friction test was 4.4×10 -5 (mm 3 / Nm)~8.0×10 -5 (mm 3 / Nm); The mass loss of the 21.99 g to 23.61 g carbon fiber reinforced composite coating after the erosion test is 0.60 g to 0.83 g.
11. Use of the carbon fiber reinforced composite coating according to claim 10 in the field of substrate protection.
12. The use according to claim 11, characterized in that: The substrate includes a steel structure facility; And / or, the application includes: application of the carbon fiber reinforced composite coating on steel structure facilities serving in ocean splash zones.
Citation Information
Patent Citations
Method for preparing carbon fibers with surfaces grafted with hyperbranched polymer
CN107266712A
Method for grafting hyperbranched aromatic polyamide to surface of carbon fibers
CN107313259A
Method for grafting curing agent imidazole on surface of carbon fiber
CN109385891A
Preparation method of hyperbranched polyester grafted carbon fiber
CN109577007A
Surface modified carbon fiber and modification method thereof
CN113322678A
Cited By
Impact-resistant and wear-resistant repair material and preparation method thereof
CN120736849A
Wear-resistant PEEK composite material and application of wear-resistant PEEK composite material in reversing valve for air bag pump
CN120737583A
Wear-resistant peek composite material and its application in reversing valve for wind bag pump
CN120737583B